Improvement in efficiency and stability of quantum dot/polymer nanocomposite film for light-emitting diodes using refractive index-controlled quantum dot–silica hybrid particles. Issue 38 (23rd August 2019) - Jeon, Hyungjoon; Jo, Joon Hee; Yang, Kab Pil; Lee, Kangtaek
Abstract : Controlling refractive index of hybrid particles suppressed light scattering and enhanced efficiency and stability of nanocomposite film. Abstract : We have synthesized silica–quantum dot (QD)–silica (SQS) hybrid particles using Cd-free InP@GaP/ZnS QDs with silica particles. The surfaces of the SQS particles were modified with phenyl groups to control the refractive index. The surface modification reduced the light scattering in the SQS particle suspension by matching the refractive index of the particles to the solvent. The resulting suspension exhibited a quantum yield close to that of the unmodified QDs. Fabrication of the nanocomposite films using the synthesized particles and poly(methyl methacrylate) (PMMA) demonstrated that the transparency and quantum efficiency of the films containing both the SQS and the phenyl-modified SQS particles were higher than those containing the unmodified QDs due to the more uniform dispersion of the QDs. In addition, the reduced light scattering in the film with the phenyl-modified SQS particles resulted in higher quantum efficiency than that with the unmodified SQS particles. Analysis after three days at 100 °C and 85% relative humidity revealed that the stability of the film containing the phenyl-modified SQS particles was superior to that with the unmodified QDs. Finally, a light-emitting diode (LED), prepared using the nanocomposite with the phenyl-modified SQS particles, displayed much higher photoluminescence intensity and efficiency than that with the unmodified SQS particles due to reduced light scattering.